Hindu Gen Z perceptions of karma and reincarnation at Denpasar City : (Gen Z hindus question the truth of the concept of karma and reincarnation?) - Si Luh Nyoman Seriadi; Ni Luh Putu Yuliani Dewi (Institute for Advanced Science Social, and Sustainable Future, 2023)
Karma and reincarnation are central concepts in Hinduism. The law of karma says that whatever humans do will be harvested accordingly. Whoever does evil will be rewarded accordingly, and those who do good will find goodness. However, the facts of life do not always follow these laws, and Gen Z states that he knows many people who do bad things but are respected in the public sphere. The evil deeds committed do not have any natural effect. They question whether religion only offers heaven's reward and whether good people have to suffer. The concept also seemed unappealing to them because a good and prosperous life on Earth is essential. Suppose a wrong person with evil behavior can achieve a good life, get rich fraudulently, get elected as an official, and be respected. In that case, it is questionable where the world's justice lies. This article is the result of qualitative research that examines the perceptions of Gen Z Hindus in the city of Denpasar regarding karma and reincarnation. Research is also combined with statistical analysis, which shows a tendency to doubt believing the truth of the concept. The study involved 200 adolescents from the city of Denpasar, with data collection carried out through observation, interviews, and FGDs and continued with filling out a simple questionnaire. The analysis results show that as many as 35% of adolescents have doubts about the truth of karma and reincarnation, 15% do not know, and the rest believe in the truth of the concept even though it leaves a number of questions.